Prevalence and molecular epidemiology of enterotoxigenic Escherichia coli in diarrhoeic neonatal and post-weaning piglets in Gauteng and North West Provinces South Africa - Fasina, Folorunso Oludayo (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.